Correction: Physiological responses and external validity of a new setting for taekwondo combat simulation - Hausen, Matheus; Soares, Pedro Paulo; Araújo, Marcus Paulo; Porto, Flávia; Franchini, Emerson; Bridge, Craig Alan; Gurgel, Jonas (PloS one, 2017)
[This corrects the article DOI: 10.1371/journal.pone.0171553.].